A Local-Content Comic Based on the Legend of I Macan Bali on Ecosystem Material to Improve Learning Outcomes of Grade V Students - Ni Putu Anik Kania Dewi; Ni Wayan Rati; Adrianus I Wayan Ilia Yuda Sukmana (Jurnal Ilmiah Sekolah Dasar, 2025)
Learning outcomes in science, particularly on ecosystem content, often remain low due to the limited use of contextual and culturally relevant learning media. Students tend to experience superficial understanding when instructional materials fail to connect with their local environment and lived experiences. This study aims to analyze the design, evaluate the validity and practicality, and examine the effectiveness of a local-content comic based on the Legend of I Macan Bali to enhance the science learning outcomes of grade V students. This research employed the ADDIE development model encompassing analysis, design, development, implementation, and evaluation stages. The subjects consisted of experts, education practitioners, and 15 students as the trial sample, while the object of the study was students’ science learning outcomes. Data were collected through observation, interviews, questionnaires, and tests, supported by validated instruments. Data analysis used a paired-sample t-test to measure the effectiveness of the developed media. The results indicate that the comic media achieved high validity, demonstrated practical use in classroom settings, and produced a significant improvement in students’ learning outcomes. The study concludes that integrating local cultural elements into instructional media not only strengthens conceptual understanding but also nurtures cultural awareness. These findings imply that teachers should meaningfully incorporate local wisdom into learning resources to create more engaging, relevant, and meaningful learning experiences.